1984
DOI: 10.1139/b84-305
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and status of Acorus (Araceae) in Canada

Abstract: Evidence is presented documenting the occurrence in Canada of two Acorus species. One is a widespread fertile diploid with which the name A. americanus has been associated. The other is a sterile taxon of more limited distribution, no doubt representing the well-known sterile triploid A. calamus of Europe, which has been widely introduced into North America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Triploids, however, can be identified based on their sterility. Packer and Ringius [18] studied the stainability of pollen from as many as about 280 herbarium specimens of Acorus from Canada and provided convincing evidence that sterile triploids can be recognized based on their nonstaining pollen. Thompson [21] studied as many as 352 specimens from North America and came to the same conclusion.…”
Section: Ploidy Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…Triploids, however, can be identified based on their sterility. Packer and Ringius [18] studied the stainability of pollen from as many as about 280 herbarium specimens of Acorus from Canada and provided convincing evidence that sterile triploids can be recognized based on their nonstaining pollen. Thompson [21] studied as many as 352 specimens from North America and came to the same conclusion.…”
Section: Ploidy Levelmentioning
confidence: 99%
“…The only way of resolving the taxonomic identity of Schott's species names is through the identification of type specimens among historical herbarium collections, by inferring characters missing in Schott's description from this material. Fortunately, earlier studies revealed clear correlations between plant fertility, leaf anatomy, and ploidy levels in Acorus [10,18,32,[35][36][37]. The use of these characters should provide a link between cytotypes and Schott's species names.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed studies of North American material (Packer & Ringius, 1984; Thompson, 1995, 2000, see also Kaplan, 1970) revealed a clear and easy‐to‐interpret pattern with two cytotypes, which were taxonomically recognized as separate species, Acorus americanus (diploid) and A. calamus (triploid). Diploids are native and mainly occur in the northern part of North America.…”
Section: Introductionmentioning
confidence: 99%